Evaluasi Postur Kerja pada Pekerja Area Workshop Menggunakan Nordic Body Map Questionnaire dan Metode Rapid Entire Body Assessment di PT X - Ari Rahman; Alfiyah Najwa; Nova Ulhasanah; Anita Juraida (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The aim of this study is to evaluate the ergonomic conditions of workers in the workshop area of PT X. The workshop area consists of five different workstations: cutting, welding, turning, painting and sanding. These workstations involve physical effort that affects muscle tissue, bones and joints, potentially leading to musculoskeletal disorders (MSDs). Our main objective was to identify the critical workstation among the five workstations in the fabrication manufacturing section of PT X. The critical workstation and working posture were analysed using the Nordic Body Map (NBM) questionnaire and the Rapid Entire Body Assessment (REBA) method. The result of the NBM questionnaire score showed that the grinding workstation had the highest score of 102, indicating its critical nature. Work posture analysis using REBA then identified workers 8 and 10 as representing the critical workstations as they had the highest NBM score. Worker 8 received a REBA score of 11, indicating a very high risk requiring immediate follow-up. In addition, worker 10 received a REBA score of 8, indicating a high risk and requiring immediate corrective action.